An Evaluation of European Union Development Aid to the Democratization Project in Cameroon. Issue 1 (2nd January 2020) - Pemunta, Ngambouk Vitalis
ABSTRACT: As a way of deepening democracy, the European Union (EU) has dedicated substantial financial and technical assistance to Cameroon's civil society and election process. More than two decades after the adoption of multipartism, there is, however, the lack of a credible institutional framework for democratization in the country. This analysis of mainly primary sources draws on donor–recipient relations theory to provide a critical assessment of the EU's aid to the democratization process in Cameroon. The article argues that the overemphasis on elections as a catalyst for orchestrating broader changes has instead given the Yaounde regime room to maneuver by failing to genuinely embrace democratization. Besides the worrying lack of institutional reforms, weaknesses embedded in the EU's aid architecture and its member state's self-interests have significantly compromised the effectiveness of its development assistance program in Cameroon and most of the Third World. The study suggests that the EU should recognize elections as a multifaceted process involving a complex cycle of myriad events and legal, technical, and organizational processes.